Absolute and Relative Reliability of a Comprehensive Quantitative Sensory Testing Protocol in Women Treated for Breast Cancer. Issue 6 (15th December 2021) - Dams, Lore; Haenen, Vincent; Van der Gucht, Elien; Devoogdt, Nele; Smeets, Ann; Bernar, Koen; De Vrieze, Tessa; De Groef, An; Meeus, Mira
Abstract: Objective: Quantitative sensory testing (QST) consists of noninvasive psychophysical assessment techniques to evaluate the functioning of the somatosensory nervous system. Despite the importance of reliability for the correct use of QST results in research and clinical practice, the relative and absolute intra- and inter-rater reliability of a comprehensive QST protocol to evaluate the functioning of both the peripheral and central somatosensory nervous system in a breast cancer population has not yet been investigated. Setting: University Hospitals, Leuven, Belgium. Subjects: Thirty women at least 6 months after unilateral breast cancer surgery. Methods: The protocol included nine static and dynamic QST methods (mechanical pain-detection thresholds, pressure pain thresholds, thermal pain-detection thresholds for heat and cold, temporal summation, and conditioned pain modulation [CPM]) performed in the surgical area and in more distant regions. Absolute and relative intra-rater reliability (60-minute interval) and inter-rater reliabilty (1-week interval) were evaluated with intraclass correlation coefficients, standard error of measurement, and Bland-Altman plots. Results: Moderate to excellent relative intra-rater reliability and inter-rater reliability were found for the evaluation of mechanical thresholds, pressure pain thresholds, and temporal summation. The reliability of the CPM paradigm was considered weak. Systematic bias between raters was noticed for the detection of mechanical and cold stimuli at the non-affected trunk and for CPM. Conclusions: Except for the evaluation of CPM, the QST protocol was found suitable for identifying differences between subjects (relative reliability) and for individual follow-up after breast cancer surgery (limited systematic bias) during a 1-week time frame. Additional research is required to determine the measurement properties that influence CPM test stability to establish a more reliable CPM test paradigm.